2016
DOI: 10.1038/ijo.2016.113
|View full text |Cite
|
Sign up to set email alerts
|

Long-term glucocorticoid concentrations as a risk factor for childhood obesity and adverse body-fat distribution

Abstract: Long-term cortisol concentrations are strongly associated with an increased risk of childhood obesity and adverse body-fat distribution. Future research may reveal whether these are causal relations and may be a target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 44 publications
4
38
1
1
Order By: Relevance
“…cortisol in hair and saliva, heart rate variability, resting heart rate and blood pressure. Evidence from observational studies using hair and saliva cortisol samples and/or blood pressure measures reveal that stress is positively related to increased BMI and specifically abdominal adiposity, both among children and adults (Table ) . These results have also been repeated in human experimental studies, where negative mood and cortisol levels increased significantly as response to acute stress sessions; high cortisol compared with low cortisol responders were significantly more negatively affected/stressed (Table ) .…”
Section: Associations Among Mental Stress Anxiety and Well‐being Anmentioning
confidence: 88%
“…cortisol in hair and saliva, heart rate variability, resting heart rate and blood pressure. Evidence from observational studies using hair and saliva cortisol samples and/or blood pressure measures reveal that stress is positively related to increased BMI and specifically abdominal adiposity, both among children and adults (Table ) . These results have also been repeated in human experimental studies, where negative mood and cortisol levels increased significantly as response to acute stress sessions; high cortisol compared with low cortisol responders were significantly more negatively affected/stressed (Table ) .…”
Section: Associations Among Mental Stress Anxiety and Well‐being Anmentioning
confidence: 88%
“…This method for assessing cortisol has advantages over traditional measures using saliva, urine or serum, because it is not vulnerable to daily fluctuations and reflects average exposure to cortisol over approximately one month per 1 cm of scalp-proximal hair . Previous studies in the ELSA cohort and other samples have documented a positive association between obesity and hair cortisol (Jackson et al, 2017;Manenschijn et al, 2011b;Noppe et al, 2016;Veldhorst et al, 2013;Wester et al, 2014), but this literature needs further development and the mechanisms underlying this association are not well understood. Relationships between perceived weight discrimination and both obesity (Jackson et al, 2015b) and hair cortisol (Jackson et al, 2016) have also been observed in ELSA, but the potential mediating role of weight discrimination has not been tested in this or any other sample.…”
Section: Introductionmentioning
confidence: 93%
“…This association may be causal, based on evidence from a controlled trial in adults showing that shorter sleep duration was followed by an elevation in cortisol levels the next evening ( 13 ). However, a few studies in children have indicated the reverse: cortisol dysregulation may precede sleep problems ( 14 , 15 , 16 ). These studies suggest that HPA dysregulation and sleep duration are associated, but the direction of effects are not clear and warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%